Tahap motivasi dan tanggapan pembaca matang terhadap naskhah terbitan Buku Fixi / Mohd Syuhaidi Abu Bakar and Norsyahirah Ngah@Muhammad - Abu Bakar, Mohd Syuhaidi; Ngah@Muhammad, Norsyahirah (2018)
Buku Fixi is one of Malaysia's indie publishing companies that actively publishing derivative works. However, there are instances and accusations that the indie publishing companies do not emphasize the values of languages in their works, leading to negative perception towards indie publishing companies and decreasing motivation to support such organizations. The objective of this study is to identify the perceptions and the level of motivation among readers of Buku Fixi. This study uses quantitative methods and involving 129 respondents selected using purposive sampling. Data is collected online using Google Forms. Data is then analyzed descriptively and represented by percentages. The results of this study show that respondents have a positive perception of Buku Fixi and they have a high motivation to continue reading the products of Buku Fixi.